A framework for the best practise in developing Java web applications with version control - Makwangudze, Simbarashe (Midlands State University, 2018)
Version Control Systems for quite some time present an integral part of development process and a must have tool for both individual developers and teams as well. However, use of version control systems and choice of proper workflow can at first be challenging. Developers and teams often do not invest enough time to get to know the possibilities of such systems, which results in these systems not being used to their full potential. The purpose of the study was to develop a framework for version control in the development of java web applications. Using a qualitative research in conjunction with design science paradigm, data was collected through semi-structured interviews, participant observation, document review and qualitative questionnaire. The analysis of data was done using structural coding to find emerging themes. The findings of the study revealed that version control was not implemented correctly and, in some situations, never used at all. This made it difficult to properly manage software releases, development teams could not effectively work together on a project and source code management needed more effort in order to combine code from different developers. In this research, I have mitigated this problem by identifying and systematizing useful tools and best practices in using version control systems. I have covered the case of Git – one of today’s most popular version control system. This study recommends that the development team should use a framework for version control to allow software developers to collaborate, developers to properly manage source code, this will in turn increase productivity and software may then be released quicker with fewer bugs.